ANALISIS PENGENDALIAN KUALITAS PRODUKSI BOGIE BARBER S2HD 9C MENGGUNAKAN METODE LEAN SIX SIGMA DENGAN PENDEKATAN DMAIC (DEFINE, MEASURE, ANALYZE, IMPROVE, CONTROL) STUDI KASUS DI PT BARATA INDONESIA (PERSERO) GRESIK - Suparno, Suparno; Hamim, Moh. Ismail; Prasetiawan, Heru (Universitas Nahdlatul Ulama Sidoarjo, 2016)
This study aimed to analyze the quality control and waste that occurs in side frame S2HD9C production using lean six sigma method with DMAIC approach in PT Barata Indonesia (Persero) Gresik. Side frame S2HD9C is a part of bogie barber S2HD9C products. This study focused on six sigma phase on defect analysis and sigma performance, while lean six sigma phase focused on the analysis of waste and sigma performance. The data used in this study are two types: primary and secondary data, qualitative and quantitative. Primary data were obtained from field observations, while secondary data obtained from the study of the document. This study conducted with the approach of DMAIC (define, measure, analyze, improve, control). After the analysis at six sigma stage, it is known that there are 5 types of defects that occur in January to April 2016, they are trapped gas defect 58.18%, broken core defect 21.82%, sand drop defect 12.73%, brake mold defect 5.46% and misplace core defect 1.82%. And sigma value achievement level of each defect are as follows: trapped gas defect 1235.71 DPMO = 4.52σ, broken core defect 463.392 DPMO = 4.81σ, sand drop defect 270.312 DPMO = 4.96σ, brake mold defect 115.848 DPMO = 5.18σ and misplace core defect 38.616 DPMO = 5.45σ. In lean six sigma stage, it is known that there are 4 types of waste, they are: waste defect product, waste waiting time (delay), waste transportation, and waste excess process. Here are achievement values of each waste: waste defect product 6890 DPMO = 3.96σ and value capability process 1.31 = 3.94σ, waste waiting time (delay) value capability process 1 = 3σ, waste transportation value capability process 1.31 = 3.94σ and waste excess process 1499.75 DPMO = 4.47σ.